Turkish Version of Kolcaba's Immobilization Comfort Questionnaire: A Validity and Reliability Study - Betül Tosun, RN, PhD; Özlem Aslan, RN, PhD; Servet Tunay, MD; Aygül Akyüz, RN, PhD; Hüseyin Özkan, MD; Doğan Bek, MD; Semra Açıksöz, RN, PhD (Elsevier, 2015)
Purpose: The purpose of this study was to determine the validity and reliability of the Turkish version of the Immobilization Comfort Questionnaire (ICQ). Methods: The sample used in this methodological study consisted of 121 patients undergoing lower extremity arthroscopy in a training and research hospital. The validity study of the questionnaire assessed language validity, structural validity and criterion validity. Structural validity was evaluated via exploratory factor analysis. Criterion validity was evaluated by assessing the correlation between the visual analog scale (VAS) scores (i.e., the comfort and pain VAS scores) and the ICQ scores using Spearman's correlation test. The Kaiser-Meyer-Olkin coefficient and Bartlett's test of sphericity were used to determine the suitability of the data for factor analysis. Internal consistency was evaluated to determine reliability. The data were analyzed with SPSS version 15.00 for Windows. Descriptive statistics were presented as frequencies, percentages, means and standard deviations. A p value ≤ .05 was considered statistically significant. Results: A moderate positive correlation was found between the ICQ scores and the VAS comfort scores; a moderate negative correlation was found between the ICQ and the VAS pain measures in the criterion validity analysis. Cronbach α values of .75 and .82 were found for the first and second measurements, respectively. Conclusions: The findings of this study reveal that the ICQ is a valid and reliable tool for assessing the comfort of patients in Turkey who are immobilized because of lower extremity orthopedic problems.